A Case Report : Massive Subdural Empyema Following Ventriculo-Peritoneal Shunt Placement in Child Patient - Lizen, Nindi; Mouza, Abdurrahman (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Background: Subdural empyema is a critical neurosurgical condition that arise from neurosurgical procedures, trauma, meningitis, sinusitis, or otogenic infection. Reported mortality rates vary from 4.4% to 24%. Ventriculoperitoneal (VP) shunt placement is one of the most common procedures and reported rates for shunt infections are relatively high. However, their association with subdural empyema is rare. Case Report: One years old boy who presented with fever, lethargy, and inability to walk was admitted to the hospital. He was undergone Vp-shunt 1 month ago because of hydrocephalus. At the time of admission, the child was alert, had a moderate right hemiparesis, and a macrocephalic appearance. An emergency CT scan showed well-circumscribed subdural empyema. Discussion: A craniotomy was performed, then thick fibrous capsule underlying the dura mater was encountered, finally the pus was totally removed. Postoperatively, he was fully alert with a marked motoric improvement. Diplococus gram positive was found. The patient was given appropriate antibiotic treatment for 3 weeks periode. Conclusion: Subdural empyema is an unusual complication of a VP-shunt. Although rare in children, it is still a neurosurgical problem. The combination of medication and surgery treatment in Subdural empyema resulted in a good response.